Efeito da variação cambial no retorno das ações em empresas brasileiras de capital aberto - Rodney Pereira de Macedo (2011)
Since the breakdown of the parity of the exchange rate between the dollar and the currencies of member countries of the Bretton Woods agreement, in the 1970s, the exchange rate floats fieely, becoming an important source of macroeconomic uncertainty. ln Brazil, the exchange Arate began floating in 1999 when it became also here, a potential market risk for companies. Accordingly, using pooled OLS data, this deseriptive-explanatory research sought to identify the impact of the fluctuation of the real on stock returns traded at the BM&FBovespa from1999 to 2010. Considering that the currency exposure may vary throughout the time, this interval was segregated into two sub-periods: from 1999 to 2004 and from 2005 to 2010. A dummy variable was included to capture idiosyncratic effects during the critical period ofinternational crisis, from September 2008 to June 2009. 271 shares (common and preferred) of 190 companies in the first subperiod and 327 shares of 236 companies in the second sub-period have becn analyzed. The results of the quantitative analysis, with statisticalsignificance at 5%, indicate that from 1999 to 2004, the shares of 17.9% of the analyzed companies lost value due to domestic currency variation, while from 2005 to 2010 this percentage was 8.1%. Considering the significance level at 10%, these percentages are, respectively, 23.7% and 18.2%. Most companies suffered negative impact, especially in the first sub-period, and it was verified even among those who exported more than 20% of its revenues. Further research in firms notes suggests that the shortterm debt denominated in foreign currency is the main determinant of these losses, indicating caution in using exports level as a single proxy for foreign exchange exposure in Brazil. The results were inconclusive in identifying in what kind of shares, common or preferred, the exchange rate has a larger effect. The metallurgy and steel sector had the largest number of companies impacted by exchange rate from 1999 to 2004, with thirteen or 65% ofthe analyzed companies affected. From 2005 to 2010, all companies surveyed in the mining and software sectors were affected. Notwithstanding the impact of foreign exchange exposure on stock returns, few companies reported their net exposure, segregated by maturity, in a formatted table which would enable straightforward assessment of the amount of assets and liabilities indexed to foreigncurrencies, as well the exposures level from exports and imports.